RANCANG BANGUN LAS (OAW) OXY ACETYLIN WELDING BERBAHAN BAKAR GAS ACETYLIN UNTUK MENINGKATKAN MINAT BELAJAR MAHASISWA TEKNIK MESIN UNIVERSITAS HASYIM ASY`ARI - Hasbi R, Ali; Eka P.S; Basuki; Satriya H, Fajar (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
This research is an experimental study, in which the researcher designed the design, then formed into aprototype weld oxy Acetylin that will be used in the practice of welding practicum. The research subject is amechanical engineering student of 2015 as many as 19 students.The results of the research showed that the building of the design of welding (OAW) Oxy Acetylin Weldingfueled Acetylin Gas works well and can increase the learning interest of mechanical engineering students onwelding courses at the University of Hasyim Asy'ari Tebuireng Jombang, this can be seen from severalindicators of interest that become judgment. The liking indicator shows a value of 77.63%, expressed interest inthe liking indicators including the high category. For interest indicators obtained 75.00% value. expressedinterest in interest indicators including high category. While the analysis results for the focusing indicator is81.58%. This expressed interest in the focused indicator including the very high category. For the activeindicators students obtained a value of 66.78%. This expressed interest in the student's active indicatorsincluding high category. Then the confidence indicator values of 80.53%. This expresses interest in theconfidence indicator including the high category. Keywords: students, welding processes, welding acetylin, learning interests